Importance of a systematic cognitive assessment: implementation of a cognitive evaluation and rehabilitation clinic in rheumatic patients - Moreno Salinas, Andrea; Corral Trujillo, María Eugenia; Hernández Galarza, Ivan de Jesús; Solís, C.V.; Leal Bramasco, A. S.; Santoyo Fexas, Leticia; Galarza Delgado, Dionicio Ángel (2020)
Cognition is the ability to learn, process and remember information to be used later. Cognitive impairment reflects a decrease in one or more cognitive domains: memory, language, reasoning, among others. It has been reported in rheumatic diseases such as systemic lupus erythematosus, rheumatoid arthritis, fibromyalgia, and it is frequently found in young patients during the first years of their illness correlating the disease progression. This condition can lead to anxiety and depression, compromising the quality of life. Given the lack of consensus regarding the best test to diagnose cognitive impairment, multiple tools have been used to address this problem.